2012
DOI: 10.1080/10934529.2012.672065
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of cadmium, mercury, zinc, copper and cobalt in the tissues of wild boar(Sus scrofa) hunted in the western Slovakia

Abstract: The aim of this study was to monitor accumulation of cadmium (Cd), mercury (Hg), zinc (Zn), copper (Cu) and cobalt (Co) in the muscle, liver and kidney of wild boar (Sus scrofa scrofa) from hunting place of western Slovakia and the correlations among the observed elements. A total of 120 samples were involved for analyses by atomic absorption spectrophotometry (AAS). The significantly highest accumulation of Cd in the kidney followed by the liver and muscles was found. Zn accumulated mainly in the liver. Signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
4
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 36 publications
3
13
4
1
Order By: Relevance
“…Nevertheless, we observed lower values than those reported by Hernández et al (1985) for cadmium in muscle (geometric means of 0.07 vs 0.12 mg Cd kg -1 w.w.) or in liver (geometric means of 0.067 vs 0.45 mg Cd kg -1 w.w.). Our data also show lower values than those reported by Gasparik et al (2012) who reported 0.16 and 3.22 mg Cd kg -1 w.w. as the mean values for muscle and kidney, respectively, and those reported by Wolkers et al (1994) who reported a median cadmium concentration of 2.05 mg kg -1 d.w. (dry weight) in liver samples of wild boar aged 1.5-5 years. Adopting a conversion factor of 3.4, the cadmium concentration reported by Wolkers et al (1994) corresponds to 0.60 mg kg -1 w.w., which is 10 times greater than the median (0.067 mg kg -1 w.w.) observed in our study.…”
Section: Cadmiumcontrasting
confidence: 90%
See 3 more Smart Citations
“…Nevertheless, we observed lower values than those reported by Hernández et al (1985) for cadmium in muscle (geometric means of 0.07 vs 0.12 mg Cd kg -1 w.w.) or in liver (geometric means of 0.067 vs 0.45 mg Cd kg -1 w.w.). Our data also show lower values than those reported by Gasparik et al (2012) who reported 0.16 and 3.22 mg Cd kg -1 w.w. as the mean values for muscle and kidney, respectively, and those reported by Wolkers et al (1994) who reported a median cadmium concentration of 2.05 mg kg -1 d.w. (dry weight) in liver samples of wild boar aged 1.5-5 years. Adopting a conversion factor of 3.4, the cadmium concentration reported by Wolkers et al (1994) corresponds to 0.60 mg kg -1 w.w., which is 10 times greater than the median (0.067 mg kg -1 w.w.) observed in our study.…”
Section: Cadmiumcontrasting
confidence: 90%
“…Considering the kidney samples analyzed, the average contamination was variable in samples from ACQ, MTI and MTO, approximately 40 mg Zn kg -1 w.w. in GRA, decreased to 30 mg Zn kg -1 w.w. in MNO, and decreased further to approximately 20 mg Zn kg -1 w.w. for the samples from NE (P<0.01). Falandysz (1994) reported average wild boar muscle values of 28-37 mg Zn kg -1 w.w. with a range oscillating between 4.3 and 130 mg Zn kg -1 w.w. Gasparik et al (2012) reported a mean value of 28.20 mg Zn kg -1 w.w.. These average data are lower than those reported in our study; however, they have a wider range (Table 3).…”
Section: Zinccontrasting
confidence: 88%
See 2 more Smart Citations
“…In contrast, Mariam et al (2004) reported Cd Gasparik et al (2012), because Cd is one of the most toxic elements to humans and animals (Naja and Volesky, 2009). Cd is toxic virtually to every system in the normal body.…”
Section: Cadmium (Cd)mentioning
confidence: 98%